Inequality, crime and property offences : a critical analysis of theft in Ireland - Ní Lionsigh, Nóra (Trinity College (Dublin, Ireland). School of Law, 2016)
Inequality, crime and property offences interact and intersect across multiple different spheres. Disentangling the relationship between them requires analysis of economics, sociology, culture, history, law and philosophy, as these phenomena interact across academic disciplines as they do across society more generally. This thesis aims to undertake this task; to understand and to contextualise these interlinked phenomena with a view to interrogating their relationship. The central research aim of this thesis is critical examination of the relationship between inequality, crime and property offences, with a particular emphasis on the offence of theft. The focus is on the nature of this relationship in Ireland in particular. While the thesis approaches this topic from a legal perspective, this is tempered by its socio-legal methodology, as it adopts an interdisciplinary approach to addressing the question as to the relationship between inequality, crime and property offences.
Keywords: Law, Ph.D.; PhD Trinity College Dublin, 2016